Development of Numerical Child Dummy model and the analysis of head impact criterion - Mohamad Sulaiman, Ibrahim; Rakhmad Arief, Siregar; Abdul Hamid, Adom; Shah Fener Khan; Hafizawati, Zakaria (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.